Point break - Bigelow, Kathryn; Reeves, Keanu; Swayze, Patrick; Busey, Gary; Petty, Lori (Burbank, CA : Warner Bros. Entertainment Inc., 2015)
A young FBI agent tries to infiltrate a group of surfer-bankrobbers dressing as ex-presidents.
Originally released as a motion picture in 1991.
Dolby digital 5.1, widescreen version presented in a "letterbox" widescreen format preserving the "scope" aspect ratio of its original theatrical exhibition; enhanced for widescreen TVs.
Features: additional scenes, 4 featurettes: It's make or break, Ride the wave, Adrenaline junkies, On location Malibu, theatrical trailer.
Music, Mark Isham ; director of photography, Donald Peterman.
Keanu Reeves, Patrick Swayze, Gary Busey, Lori Petty.
MPAA rating: R.
Keywords: United States. -- Federal Bureau of Investigation -- Drama; Bank robberies -- Drama; Criminal investigation -- Drama; Action and adventure films; Crime films; Video recordings for the hearing impaired; Fiction films; Feature films